Fluid Characteristics at Material for Porous Lateral Pipe with Via-Flow Method at Trickle Irrigation - Netty Kurniadi; Dedi Kusnadi; Nora Herdiana Pandjaitan (PERTETA, 2000)
This research tries to find a suitable material for porous lateral pipe, its mean outflow, its coefficient of uniformity and distribution of outflow along the pipe. The material that is used in this research is Parachute and Fatnatex cloth with 20 cm long.The research shows that the Famatex cloth with 8 cm circumference, gives a better performance and can be used for the further research . Besides. the bigger head is used, the faster water flow and the bigger mean outflow from the material to the ground surface.